Doxorubicin-conjugated CuS nanoparticles for efficient synergistic therapy triggered by near-infrared light. Issue 12 (17th February 2016) - Bi, Huiting; Dai, Yunlu; Lv, Ruichan; Zhong, Chongna; He, Fei; Gai, Shili; Gulzar, Arif; Yang, Guixin; Yang, Piaoping
Abstract : A CuS–DOX NP drug delivery system was synthesized by conjugating carboxyl-functionalized copper sulfide nanoparticles (CuS NPs) and DOX through hydrazone bonds. The platform exhibits high in vitro and in vivo anti-cancer efficacy due to the combined chemo- and photothermal therapeutic effect upon 808 nm laser irradiation. Abstract : To integrate photothermal therapy (PTT) with chemotherapy for improving anticancer efficiency, we developed a novel and multifunctional doxorubicin (DOX) conjugated copper sulfide nanoparticle (CuS–DOX NP) drug delivery system using hydrazone bonds to conjugate carboxyl-functionalized copper sulfide nanoparticles (CuS NPs) and DOX. On the other hand, the hydrazone bonds could be used for improving the DOX release rate (88.0%) by cleavage in a mildly acidic environment irradiated by 808 nm laser light, which could greatly promote chemo-therapeutic efficacy. Simultaneously, CuS NPs which can absorb near infrared (NIR) light produce a clear thermal effect, giving rise to a synergistic therapeutic effect combined with enhanced chemo-therapy. The DOX-conjugated CuS NPs display an evident in vitro cytotoxicity to HeLa cancer cells under 808 nm light irradiation. High tumor inhibition efficacy has been achieved after 14 day in vivo treatment, performed with intravenous administration of CuS–DOX NPs with 808 nm laser irradiation on H22 tumor-bearing mice. The multifunctional system which was achieved by a facile route should be a potential candidate in the anti-cancer field due to the synergistic therapeutic effect, which is superior to any single approach.